Strategi Menggambar Terhadap Long-Term Memory Dalam Menghafal Istilah dan Definisi - Kusuma, Perdana; Adnan, Rifqah Athifah Imran; Novelia, Sri; Lestari, Nuri; K., A. Maura Azzahra (HUMAN: South Asian Journal of Social Studies, 2024)
Abstract. The topic of memorization strategies, particularly drawing, has been extensively researched. Drawing definitions, as evidenced by previous studies, has been found to be more effective in memorizing definitions compared to verbatim writing. This research is crucial as it equips students with effective memorization strategies for their lectures. In this study, the researchers sought to investigate the influence of drawing strategies on students' memory of terms and definitions. The research was conducted on 36 randomly selected students using an experimental design within-subject posttest only design. The results of the experimental studies reveal that drawing is more effective than writing verbatim in remembering definitions. These findings have practical implications, suggesting that students can consider using the drawing method as an alternative to facilitate the memorization of definitions.Keywords: memorization strategies, long-term memory, learning strategy